Considerations to Support Use of PROMIS Pediatric Measures in Ambulatory Clinics - Cox, Elizabeth D. (J Pediatr, 2020)
OBJECTIVE: To identify challenges to the use of Patient-Reported Outcomes Measurement Information System (PROMIS) Pediatric measures in the ambulatory pediatric setting and possible solutions to these challenges. STUDY DESIGN: 18 semi-structured telephone interviews of health system leaders, measurement implementers, and ambulatory pediatric clinicians were conducted. Five coders used Applied Thematic Analysis to iteratively identify and refine themes in interview data. RESULTS: Most interviewees had roles in leadership or the implementation of patient-centered outcomes; 39% were clinicians. Some had experience using PROMIS clinically (44%) and 6% were considering this use. Analyses yielded six themes: 1) selection of PROMIS measures, 2) method of administration, 3) use of PROMIS Parent Proxy measures, 4) privacy and confidentiality of PROMIS responses, 5) interpretation of PROMIS scores, and 6) using PROMIS scores clinically. Within the themes, interviewees illuminated specific unique considerations for using PROMIS with children, including care transitions and privacy. CONCLUSIONS: Real world challenges continue to hamper PROMIS use. Ongoing efforts to disseminate information about the integration of PROMIS measures in clinical care is critical to impacting the health of children.